2017
DOI: 10.1093/brain/awx070
|View full text |Cite
|
Sign up to set email alerts
|

Focal CA3 hippocampal subfield atrophy following LGI1 VGKC-complex antibody limbic encephalitis

Abstract: Autoantibodies linked with voltage-gated potassium channel (VGKC)-complex antibody-mediated limbic encephalitis (LE) bind to hippocampal subfields. Miller et al. report that chronic LGI1 antibody VGKC-complex LE is associated with focal CA3 atrophy on 7.0-Tesla neuroimaging and autobiographical episodic amnesia. The results point to antibody-mediated pathogenicity and CA3-mediated impairment of episodic memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
80
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 29 publications
(46 reference statements)
20
80
1
Order By: Relevance
“…In line with previous reports of this patient population (Dalmau and Rosenfeld, 2014;Miller et al, 2017), manual (blinded) segmentation of the hippocampi from high-resolution structural MRI scans confirmed that our patients showed volume loss confined to the left (Patients -HPC: 2506mm 3 (mean) +/-394 (standard deviation), control participants -CTL: 3173 mm 3 +/-339, W=4.0, p=0.002) and right (HPC: 2678mm 3 +/-528, CTL: 3286mm 3 +/-301, W=8.0, p=0.01) hippocampus. To rule out pathological differences between patients and controls elsewhere in the brain, an automated voxel-based-morphometry (VBM; Ashburner, 2009) analysis was carried out on whole brain T1 weighted MRI images and, in line with previous reports on patients of this sort (Wagner et al, 2015;Finke et al, 2017;Miller et al, 2017), did not result in any significant group differences outside of the hippocampus even at a liberal uncorrected p-value of less than 0.001. Neuropsychologically, the patients displayed an impairment in immediate and delayed recall on the Logical Memory (short stories) test (Wechsler, 1997), and they recollected significantly fewer episodic ('internal'), but not semantic ('external') details on the Autobiographical Interview , as detailed in Table 2.…”
Section: Participantssupporting
confidence: 92%
“…In line with previous reports of this patient population (Dalmau and Rosenfeld, 2014;Miller et al, 2017), manual (blinded) segmentation of the hippocampi from high-resolution structural MRI scans confirmed that our patients showed volume loss confined to the left (Patients -HPC: 2506mm 3 (mean) +/-394 (standard deviation), control participants -CTL: 3173 mm 3 +/-339, W=4.0, p=0.002) and right (HPC: 2678mm 3 +/-528, CTL: 3286mm 3 +/-301, W=8.0, p=0.01) hippocampus. To rule out pathological differences between patients and controls elsewhere in the brain, an automated voxel-based-morphometry (VBM; Ashburner, 2009) analysis was carried out on whole brain T1 weighted MRI images and, in line with previous reports on patients of this sort (Wagner et al, 2015;Finke et al, 2017;Miller et al, 2017), did not result in any significant group differences outside of the hippocampus even at a liberal uncorrected p-value of less than 0.001. Neuropsychologically, the patients displayed an impairment in immediate and delayed recall on the Logical Memory (short stories) test (Wechsler, 1997), and they recollected significantly fewer episodic ('internal'), but not semantic ('external') details on the Autobiographical Interview , as detailed in Table 2.…”
Section: Participantssupporting
confidence: 92%
“…Hence, this increasingly well‐characterized group of patients may represent an important neuropsychological model of disrupted functional connectivity whose critical locus resides within the hippocampus. This is broadly consistent with other studies who have reported selective hippocampal damage in VCKCC_Ab LE patients, perhaps even at the level of the hippocampal subfields (Miller et al, ). As such, future neuropsychological studies with VCKCC_Ab LE patient cohorts, in combination with studies utilizing high‐resolution structural and functional MRI and advanced analytical methods, could offer important traction on many of the entrenched impasses firmly rooted in the hippocampal literature.…”
supporting
confidence: 92%
“…This dissociation is consistent with the recently reported dissociation F I G U R E 1 Structure MRI of patients from initial presentation in the acute phase (T2 coronal FLAIR; left column) and at time of neuropsychological testing in the acute phase (T1 coronal; right column). White arrows indicate increased signal intensity in the left column and subsequent atrophy in the right column (as reported by neuroradiologists) between episodic and semantic memory impairment/preservation observed in a group of 16 LGI1-VGKCC-Ab LE patients (Miller et al, 2017). Moreover, at the group level, and contrary to the standard consolidation model, our VGKCC-Ab LE patients demonstrated no temporal-gradient when recalling past personal memories.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…For example, some studies suggest that DG and CA 2/3 , respectively, subserve pattern separation and completion, although there is disagreement about this distinction (Chadwick et al, ; Guzowski, Knierim, & Moser, ; Myers & Scharfman, ; Yassa & Stark, ). Evidence from healthy adults (Chadwick et al, ; Hebscher et al, in press) and patients (Miller et al, ) for the role of CA 2/3 or CA 3 alone in episodic memory and AM suggests that our results may be accounted for by the CA 3 region and not the DG.…”
Section: Introductionmentioning
confidence: 62%